Study of coronary artery dominance in Nepalese population by angiographic method - Karna, Arun Kumar; Maskey, Arun; Nepal, Himanshu; Yadav, Dharma Nath (Nepalese Heart Journal, 2017)
Background and Aims: Coronary artery disease is one of the major causes of death in developed countries. The aim of this study was to determine the pattern of coronary artery dominance in our Nepalese population by coronary angiography method and its correlation with the extent of coronary artery disease. Methods: A six-month hospital based prospective observational study of 220 patients (from August 2016 to January 2017) of either gender of 18 years of age or more, eligible for coronary angiography for diagnostic purpose, were performed in this study. The patients with valvular heart disease, congenital heart disease were excluded. The sociodemographic profile of the patients, pattern of coronary artery dominance and its association with coronary artery diseases were all recorded on a proforma. The data were subjected to statistical analysis. Results: A total of 220 patients, 66.82% (n=147) were male and 33.18% (n=73) were female. The mean age was 59.11±11.61 years. The age range was 34-81 years. There was no in-hospital mortality. Right coronary artery was dominant in 85.5%, left dominant in 10 % and co-dominant in 4.5% of the patient population. Abnormal ECG (du to ST-T changes) was 68.18% in left dominant and 42.02% in right dominant. The chance of having coronary artery disease with abnormal ECG (due to ST-T changes) compared to normal ECG is 24 times more in left dominant and 3.875 times more in right dominant. Conclusions: The right coronary dominant pattern is more prevalent in our population. There is no significant association of age and sex with coronary dominance. The Left coronary dominant pattern is more associated with the presence of coronary artery diseases. Nepalese Heart Journal 2017; 14(2): 25-30